Kerala’s Mahabharata on Stage: Texts and Performative Practices in Kutiyattam Drama - Bruce M. Sullivan (The Journal of Hindu Studies, 2010)
This article concerns the performance of Kūṭiyāṭṭam enactments of Mahābhārata narratives and the written texts on which those performances are based. The Kūṭiyāṭṭam tradition of Sanskrit drama enactment in Kerala has been recognised by UNESCO as a ‘masterpiece of the oral and intangible heritage of humanity’ but is also profoundly concerned with written texts. I argue that the ways Kūṭiyāṭṭam performers have modified and elaborated upon the dramas’ texts have resulted in enactments more devotionally oriented than are the texts themselves, and that this distinctively devotional performative practice has contributed to the tradition’s longevity. I also argue that performances in secular settings in recent decades represent both an opportunity and a danger to the tradition.